Pemaknaan Fanbase Terhadap Isu-Isu Politik Dalam Lagu Bergenre Indie Rock - Ijlal Hibatullah, Alif; Dwiningtyas Sulistyani, Hapsari; Rahardjo, Turnomo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This research aims to understand how the fanbase of .Feast, an Indonesian indie rock band, interprets political issues conveyed through their songs. Employing a qualitative approach with ethnography of communication method, this study examines the interactions and interpretations of the